Pengaruh Manajemen Laba Terhadap Kinerja Keuangan pada perusahaan sub sektor industry and beverage yang terdaftar di bursa efek Indonesia (BEI) - Jamilah, Jamilah; Mazni, Afdal (Jurnal Manajemen DIVERSIFIKASI, 2021)
The purpose ofthis study was to determine the effectofearnings managementonfinancialperformanceinthefoodandbeverageindustry sub-sectorcompaniesin2017-2019.Samplinginthisstudyusedapurposive sampling technique in which the researchergave certain criteria,and samplesthatmatchedthecriteriaamountedto15samplesandwillbe testedusingSPSS24.0. Thetypeofresearchusedisquantitativeresearchwiththeaim of determiningtheeffectbetweenvariablesinapopulationdeterminedthrough scientificcalculationsderivedfrom thecalculationofaccrualvalues,total accruals,nondiscretionary.TocalculateprofitorROAbyfindingthevalueof netincomeaftertaxwhichwillbedividedbytotalassets/assets. Theresultsofthisstudyindicatethatearningsmanagementhasa significanteffectonreturnonassets.Itcanbeseenfromthetcountvalueof 2.436andttable2.179,whichmeansthattcountisgreaterthanttable.Soit canbeexplainedthatprofitmanagementinthefoodandbeverageindustry sub-sectorcompanieslistedontheIDXin2017-2019hasasignificanteffect onfinancialperformance.Whereearningsmanagementdescribestheeffect oreffectofcashincomeandexpenditurestoensurethatthebusiness generatesnetoperatingincome. Keywords:EarningsManagement,FinancialPerformance,ReturnOnAssets (ROA)